ECONOMIC VIABILITY OF GREEN HYDROGEN VS. OTHER RENEWABLE ENERGY SOURCES: A LEGAL ANALYSIS - SINGH, SIDDHI; JASWAL, PROF. (DR.) S. S. (South Eastern European Journal of Public Health, 2025)
The need to address climate change, improve energy security, and guarantee sustainable growth is causing a radical upheaval in the global energy sector. The progressive shift away from fossil fuels and toward renewable energy sources is what defines this transition, which has significant effects on the environment, economies, and communities. Through a legal perspective, this study compares the economic feasibility of green hydrogen to other renewable energy sources like solar, wind, and bioenergy. With an emphasis on India's National Green Hydrogen Mission, this study examines the cost structures, scalability, and regulatory frameworks influencing the global adoption of green hydrogen. In addition to discussing legislative incentives and legal issues including land and water use, environmental compliance, and intellectual property rights in technology innovation, the analysis highlights important economic considerations like production costs, infrastructure needs, and market preparedness. The potential of green hydrogen to aid in decarbonisation alongside more established renewables is examined in this research, which highlights the importance of strong legal and regulatory frameworks in promoting cost parity and deployment scaling. To increase green hydrogen's economic competitiveness in a constantly changing energy landscape, recommendations include harmonizing regulations, promoting international cooperation, and strengthening public and private partnerships.